Dilemmas, Debates, and Development of BRI in the Himalayan Nation: A Nepali Perspective - Chand, Hari Prakash (Journal of Foreign Affairs, 2023)
Nepal-China-India relations from BRI perspective is complex. Nepal joined the BRI in 2017 whereas India has not joined officially yet. But India is a founding member of the Asian Infrastructure Investment Bank (AIIB) which generally provides loans to the countries along the BRI route. Though Nepal is a part of BRI, the projects signed under the BRI are still in dilemma due to the diverse views from Nepali and Chinese sides. Against this backdrop, this paper is focused on assessing the BRI relations with Nepal and India. Moreover, the paper has assessed why India has not joined BRI and why Nepal could not implement the BRI projects even after five years of the BRI agreement. In doing so, the paper is basically descriptive under the qualitative method and no theory testing approach is adopted due to the nature of the topic of the paper. The paper concludes that Nepal should revisit its approaches and policies to effectively conduct BRI diplomacy for the sake of national pride and benefits even in Nepal-China-India complex BRI relations.